Barriers and facilitators perceived by women while homeless and pregnant in accessing antenatal and or postnatal healthcare: A qualitative evidence synthesis. (8th March 2020) - McGeough, Christine; Walsh, Aisling; Clyne, Barbara
Abstract: Evidence indicates that homelessness is increasing within Europe and the United States (US), particularly for women. Pregnancy rates among homeless women are exceptionally high compared to their housed counterparts and homeless women engage poorly with antenatal care. The aim of this review is to explore the barriers and facilitators perceived by homeless women, while pregnant, or within six weeks postpartum in accessing antenatal and/or postnatal healthcare. A qualitative systematic review and synthesis was conducted. Key words and search terms were derived using the SPIDER (Sample, Phenomenon of Interest, Design, Evaluation, Research type) framework. Titles and abstracts were screened in accordance with inclusion and exclusion criteria. The methodological quality of included papers was assessed using criteria described by the Critical Appraisal Skills Programme (CASP) with data analysis using thematic synthesis. Two primary linked themes were generated: (a) lack of person‐centred care; (b) complexity of survival. At an organisational level, a fragmented health service and accessibility to the health system were barriers, and resulted in poor person‐centred care. At a clinical level, attitude & treatment from healthcare providers together with health knowledge all combined to illustrate poor person‐centred care as barriers to homeless women accessing antenatal/postnatal healthcare. Sub‐themes associated with complexity of survival included: disillusion with life, distrust of services, competing lifestyle demands and support and relationships. The findings of this review highlight that poor engagement may be partly explained by the complex interplay between both the healthcare system (person‐centred care) and the individual (complexity of survival). Future services should be delivered in a way that recognises homeless people's complex and diverse needs, and should be reconfigured in order to try to meet them, through decreasing fragmentation of health services and staff training.